“The glint of catastrophe”. An Interview with Mohsin Hamid - Mohsin Hamid; Paul Veyret (Angles, 2022)
In August 2020, as the whole world was still reeling from the human and economic effects of the Covid-19 pandemic, Paul Veyret interviewed Mohsin Hamid through Zoom at his home in Lahore. The conversation started off with considerations on the limits and politically fraudulent nature of Imran Khan’s “Naya Pakistan”, then embarked upon an exploration of Mohsin Hamid’s four novels, Moth Smoke, The Reluctant Fundamentalist, How to Get filthy Rich in Rising Asia and Exit West. Hamid develops his view on Pakistani fiction, the different crises the emerging nations are undergoing, and how Sufi philosophy and Italo Calvino underpin his writing.